PSYCHOLINGUISTIC ANALYSIS OF COMMUNICATIVE PERSONALITY OF CADETS. - Pavlova , O. (Problems of Engineer-Pedagogical Education, 2021)
This article explains the concept of communicative personality from the perspective of psycholinguistics and communication theory. The main parameters of the communicative personality are determined based on its individual properties and characteristics, its degree of communicative needs, her cognitive skills and communicative competence in the perception and processing of new information; differential characteristics and peculiarities of linguistic communicative behavior of the individual in society. The author underlines three key parameters, defining the character of cadet’s communicative personality (motivational, cognitive and functional), highlights the important component in the process of communicative personality development (a stage of education), as professionalization of a personality takes place, all necessary professional competencies, behavioural norms and values, ideals and, internal structures of a personality are developed. This stage is marked by the acquisition of the language for specific purposes that mean the professional linguistic consciousness is developed. Drawing on research of the military discourse, the author has allocated the texts, influencing language consciousness of the military (professional and motivational); defined the key characteristics and peculiarities of cadet’s speech. The common language, physical and intellectual activities, habits and customs identify the representatives of military professional subculture. The language of military personnel of any country includes two key subsystems that may create difficulties for misguided person of the given professional environment: terminology (regulated by official documents) and slang. These subsystems are replete with different kinds of abbreviations, because one distinctive feature of military language is brevity. The article stresses that active using abbreviation in forming the military terms, in the language used for business, as well as widespread distribution of abbreviation in spoken language have an impact on the forming the slangy speech of cadets. Therefore, abbreviation is widely using in the cadets’ speech and spreading from the language of official and scientific sphere to the spoken language and slang. The article concludes that the familiarity with the abovementioned characteristics of the communicative personality of cadets is key to providing good understanding language perception of the given professional group. Structural integrity of communicative personality permits consideration of cadets in the training process with regard to their readiness to implement the communication as consistency of language system and communicative situation